Alternate wetting and drying (AWD) on rice irrigation - Abu Hassan, Nur Hidayu; Fazlil Ilahi, Wan Fazilah; Che’Ya, Nik Norasma; Ismail, Mohd Razi; Berahim, Zulkarami; Zakaria, Nurul Idayu; Omar, Mohamad Husni (Universiti Putra Malaysia Press, 2022)
In Malaysia, numerous methods have been subsequently established subjected to water-saving irrigation aiming to improve the common conventional irrigation system. However, among the most preferred water-saving method, alternate wetting and drying (AWD) irrigation adoption are presently in paddy cultivation yet has very limited information, especially locally. Hence, this study intended to propose two treatments, namely continuously flooded (control) and AWD irrigation, to investigate the feasibility of AWD implementation. The experiment was conducted at the paddy field of Padang Raja Kelantan, Malaysia. From the result, the agronomic performance was evaluated by several attributes under the growth performance evaluation, grain yield performance evaluation, and chlorophyll measurement. Statistical analysis was performed on the obtained data, and both growth, yield performances, and chlorophyll content resulted in no significant difference at p < 0.05, a 95% confidence level.